Longitudinal study of the cutaneous microbiota of healthy horses. Issue 5 (24th June 2021) - O'Shaughnessy‐Hunter, Laura C.; Yu, Anthony; Rousseau, Joyce D.; Foster, Robert A.; Weese, J. Scott
Abstract : Background: Next‐generation sequencing techniques have revealed that human and animal skin is colonised by a rich and diverse population of bacteria, and that microbial composition varies between different body sites and individuals. Very little is known about the normal microbiota of healthy equine skin. Hypothesis/Objectives: To describe the taxonomic distributions of cutaneous bacterial microbiota in a population of healthy horses in Ontario, Canada, and to evaluate the effects of body site, individual and time of year on microbial diversity and community composition. Animals: Samples were collected from four body sites (dorsum, ventral abdomen, pastern and groin) from 12 clinically healthy horses from the same farm. Samples were collected from all individuals at four time points (winter, spring, summer, autumn) within a calendar year. Methods and materials: Illumina sequencing of the V4 region of the 16S rRNA gene was performed following DNA extraction. Data were analysed using mothur software. Results: Bacteria from 38 phyla and 1, 665 genera were identified. Alpha diversity was higher in the winter and summer than spring and autumn although this was not statistically significant. Community membership and structure clustered more based on season than skin site. Conclusions and clinical importance: Healthy equine skin is inhabited by a marked diversity of microbiota. Individuals living in a similar environment share overlapping cutaneous microbial populations. These populations vary significantly over time and between body sites. Abstract : Background – Next‐generation sequencing techniques have revealed that human and animal skin is colonised by a rich and diverse population of bacteria, and that microbial composition varies between different body sites and individuals. Very little is known about the normal microbiota of healthy equine skin. Hypothesis/Objectives – To describe the taxonomic distributions of cutaneous bacterial microbiota in a population of healthy horses in Ontario, Canada, and to evaluate the effects of body site, individual and time of year on microbial diversity and community composition. Conclusions and clinical importance – Healthy equine skin is inhabited by a marked diversity of microbiota. Individuals living in a similar environment share overlapping cutaneous microbial populations. These populations vary significantly over time and between body sites. Résumé: Contexte: Les techniques de séquençage de dernière génération ont révélé que la peau de l'homme et de l'animal est colonisée par une population riche et variée de bactéries et que la composition microbienne varie entre les différents sites corporels et entre individus. On en sait très peu sur le microbiote de la peau du cheval sain. Hypothèses/Objectifs: Décrire les distributions taxonomiques du microbiote bactérien cutané d'une population de chevaux sains en Ontario, Canada et évaluer les effets du site corporel, de l'individu et de la période de l'année sur la diversité microbienne et la composition communautaire. Sujets: Les échantillons ont été prélevés sur quatre sites corporels (dos, abdomen ventral, paturons et aine). De 12 chevaux cliniquement sains de la même ferme. Les échantillons ont été prélevés pour tous les individus à quatre périodes (hiver, printemps, été, automne) d'une même année. Matériels et méthodes: Le séquençage par Illumina de la région V4 du gêne 16S ARNr a été réalisé à la suite de l'extraction d'ADN. Les données ont été analysées par programme MOTHUR. Résultats: Les bactéries de 38 phyla et 1 665 genres ont été identifiées. La diversité alpha était plus élevée en hiver et été qu'au printemps et automne bien que ceci ne soit pas statistiquement significatif. L'appartenance et la structure de la communauté étaient groupées davantage à partir de la saison que du site cutané. Conclusions et importance clinique La peau de cheval sain est habituée par une diversité marquée de microbiote. Les individus vivant dans un environnement semblable partage des populations cutanées de microbiote se superposant. Ces populations varient significativement au cours du temps et entre les sites corporels. Resumen: Introducción: las técnicas de secuenciación de próxima generación han revelado que la piel humana y animal está colonizada por una población rica y diversa de bacterias, y que la composición microbiana varía entre diferentes lugares del cuerpo e individuos. Se sabe muy poco sobre la microbiota normal de la piel equina sana. Hipótesis/Objetivos: describir las distribuciones taxonómicas de la microbiota bacteriana cutánea en una población de caballos sanos en Ontario, Canadá, y evaluar los efectos de la localización corporal, el individuo y la época del año sobre la diversidad microbiana y la composición de la microflora. Animales: Se recolectaron muestras de cuatro zonas del cuerpo (dorso, abdomen ventral, cuartilla e ingle) de 12 caballos clínicamente sanos de la misma granja. Se obtuvieron muestras de todos los individuos en cuatro momentos (invierno, primavera, verano, otoño) en un año de calendario. Métodos y materiales: se realizó la secuenciación de Illumina de la región V4 del gen de RNAr 16S después de la extracción de DNA. Los datos se analizaron con el software MOTHUR. Resultados: se identificaron bacterias de 38 phyla y 1, 665 géneros. La diversidad alfa fue mayor en invierno y verano que en primavera y otoño, aunque esto no fue estadísticamente significativo. La diversidad y la estructura de la comunidad se agruparon más según la estación que la localización de la piel. Conclusiones e importancia clínica: La piel sana de equinos está habitada por una marcada diversidad de microbiota. Los individuos que viven en un entorno similar comparten poblaciones microbianas cutáneas superpuestas. Estas poblaciones varían significativamente con el tiempo y entre los sitios del cuerpo. Zusammenfassung: Hintergrund: Die Next‐Generation‐Sequencing Techniken haben gezeigt, dass die menschliche wie auch die tierische Haut von einer reichen und diversen Bakterienpopulation kolonisiert wird und dass die mikrobielle Zusammensetzung zwischen den unterschiedlichen Körperstellen und den Individuen variiert. Es ist sehr wenig bekannt über das normale Mikrobiom der gesunden Pferdehaut. Hypothese/Ziele: Die Beschreibung der taxonomischen Verteilung der kutanen bakteriellen Mikrobiome in einer gesunden Pferdepopulation in Ontario, Kanada, sowie die Evaluierung der Einflüsse von Körperstellen, Individuen und Jahreszeit auf die mikrobielle Diversität und Zusammensetzung. Tiere: Bei 12 klinisch gesunden Pferden derselben Farm wurden Proben von vier Körperstellen genommen (Rücken, ventrales Abdomen, und Sprunggelenke und Leiste). Es wurden von allen Individuen zu vier Zeitpunkten (Winter, Frühling, Sommer, Herbst) innerhalb eines Kalenderjahres Proben genommen. Methoden und Materialien: Illumina Sequenzierung der V4 Region des 16S rRNA Gens wurde nach DNA Extraktion durchgeführt. Die Daten wurden mittels MOTHUR Software analysiert. Ergebnisse: Bakterien von 38 Phyla und 1.665 Genera wurden identifiziert. Die Alpha Diversität war im Winter und Sommer höher als im Frühling und im Herbst, obwohl dies nicht statistisch signifikant war. Die Community Mitgliedschaft und Struktur trat je nach Saison, nicht aber Körperstelle, gehäuft auf. Schlussfolgerungen und klinische Bedeutung: Gesunde Pferdehaut wird von deutlich unterschiedlichen Mikrobiota bewohnt. Individuen, die in einer ähnlichen Umgebung wohnen, teilen diese kutanen Mikrobiota. Diese Populationen variieren mit der Zeit und zwischen Körperstellen signifikant. 要約: 背景: 次世代シーケンシング技術により、ヒトや動物の皮膚には豊富で多様な細菌群が生息しており、微生物の構成は身体の部位や個人によって異なることが明らかになった。健常馬の皮膚の正常な微生物叢についてはほとんど知られていない。 仮説・目的: 本研究の目的は、カナダ・オンタリオ州の健常馬集団における皮膚細菌微生物叢の分類学的分布を明らかにし、体の部位、個体、時期が微生物の多様性および群集組成に及ぼす影響を評価することであった。 供試動物‐同: 牧場の臨床的に健常な馬12頭の4部位 (背、腹、前脚、鼠径部) からサンプルを採取した。サンプルは、1暦年内の4時点 (冬、春、夏、秋) ですべての個体から採取した。 材料と方法: 16S rRNA遺伝子のV4領域のイルミナシークエンス法を、DNA抽出後に実施した。データはMOTHURソフトウェアを用いて解析した 結果: 38門、1, 665属の細菌が同定された。α多様性は、春と秋よりも冬と夏の方が高かったが、これは統計的には有意ではなかった。群集の構成および構造は、皮膚の部位よりも季節に基づいてクラスター化していた。 結論と臨床上の重要性: 健常馬の皮膚には、顕著な多様性を持った微生物が生息している。同じような環境で生活している個体は、皮膚の微生物集団が重複している。これらの個体群は、時間の経過とともに、また体の部位間で大きく変化する。 摘要: 背景‐新: 代测序技术揭示了人类和动物皮肤被丰富多样的细菌群定植, 并且不同身体部位和个体之间的微生物组成不同。对健康马皮肤的正常微生物群知之甚少 假设/目的: 描述加拿大安大略省健康马种群中皮肤细菌微生物区系的分类分布, 并评价身体部位、个体和一年中的时间对微生物多样性和群落组成的影响。 动物‐从同: 农场的12匹临床健康马的4个身体部位 (背部、腹侧腹部、胸骨和腹股沟) 采集样本。在一个日历年内的4个时间点 (冬季、春季、夏季、秋季) 采集所有个体的样本。 方法和材料: DNA提取后对16S rRNA基因V4区进行Illumina测序。使用Mothur软件分析数据。 结果: 鉴定出38个门和1665个属的细菌。冬季和夏季的α多样性高于春季和秋季, 但无统计学意义。微生物种类和聚集结构更多地基于季节而不是皮肤部位。 结论和临床重要性: 健康马皮肤的微生物区系定植呈现着显著多样性。生活在相似环境中的个体, 其皮肤微生物种群具有相似性。这些微生物群随时间和身体部位发生着显著变化。 Resumo: Contexto: As técnicas de sequenciamento de última geração demonstraram que a pele humana e animal é colonizada por uma população rica e diversa de bactérias e que a composição microbiana varia entre diferentes áreas corpóreas e indivíduos. Muito pouco se sabe sobre a microbiota normal da pele equina saudável. Hipótese/Objetivos: Descrever as distribuições taxonômicas da microbiota cutânea bacteriana em uma população de cavalos saudáveis em Ontário, Canadá, e avaliar os efeitos da topografia corpórea, indivíduo e época do ano na diversidade microbiana e composição da comunidade. Animais: As amostras foram coletadas de quatro áreas corpóreas (dorso, abdômen ventral, quartelas e virilha) de 12 cavalos clinicamente saudáveis da mesma fazenda. As amostras foram coletadas de todos os indivíduos em quatro tempos experimentais (inverno, primavera, verão, outono) dentro de um ano civil. Métodos e materiais: O sequenciamento Illumina da região V4 do gene 16S rRNA foi realizado após a extração do DNA. Os dados foram analisados usando o software MOTHUR. Resultados: Foram identificadas bactérias de 38 filos e 1.665 gêneros. A alpha‐diversidade foi maior no inverno e verão do que na primavera e no outono, embora isso não tenha sido estatisticamente significativo. As relações filogenéticas e a estrutura da comunidade se agruparam de acordo com a estação do ano do que com a topografia corpórea. Conclusões e importância clínica: A pele saudável dos equinos é habitada por microbiota bastante diversa. Indivíduos que vivem em um ambiente semelhante compartilham populações microbianas cutâneas sobrepostas. Essas populações variam significativamente ao longo do tempo e entre as áreas corpóreas.